2022
DOI: 10.1017/s0033291722000356
|View full text |Cite|
|
Sign up to set email alerts
|

Cost-effectiveness analysis of lemborexant for treating insomnia in Japan: a model-based projection, incorporating the risk of falls, motor vehicle collisions, and workplace accidents

Abstract: Background Lemborexant has demonstrated statistically significant improvements in sleep onset and sleep maintenance compared with placebo and zolpidem tartrate extended release, measured both objectively using polysomnography and subjectively using sleep diaries, in the phase 3 clinical trial SUNRISE 1. This study evaluated the cost-effectiveness of lemborexant compared with suvorexant, zolpidem immediate release (IR), and untreated insomnia. Methods A decision-tree model was developed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…One retrospective case-crossover [ 64 ] and one cohort study [ 63 ] ran economic evaluations concurrently. Twenty-five studies were model based, 14 using a Markov model [ 53 , 56 , 65 , 67 71 , 73 , 75 , 77 , 78 , 80 , 98 ], five using a decision-tree model [ 74 , 104 107 ], one using both Markov and decision-tree models [ 76 ], one using a semi-Markov model [ 79 ] and one using a decision analytic model [ 81 ]. Additionally, two studies used randomised controlled trial-based modelling [ 94 , 108 ], and one used a case-control-based model [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One retrospective case-crossover [ 64 ] and one cohort study [ 63 ] ran economic evaluations concurrently. Twenty-five studies were model based, 14 using a Markov model [ 53 , 56 , 65 , 67 71 , 73 , 75 , 77 , 78 , 80 , 98 ], five using a decision-tree model [ 74 , 104 107 ], one using both Markov and decision-tree models [ 76 ], one using a semi-Markov model [ 79 ] and one using a decision analytic model [ 81 ]. Additionally, two studies used randomised controlled trial-based modelling [ 94 , 108 ], and one used a case-control-based model [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
“…The included studies were conducted mainly in the UK ( n = 12) [ 35 , 60 62 , 65 , 66 , 70 73 , 93 , 97 ], USA ( n = 11) [ 74 , 75 , 78 , 79 , 90 , 94 , 98 , 100 , 106 , 108 , 110 ] and Spain ( n = 10) [ 53 58 , 64 , 82 , 83 , 89 ]. Japan [ 76 , 92 , 104 , 105 ] and Canada [ 68 , 77 , 80 , 101 ] each had four studies, The Netherlands had three studies [ 59 , 95 , 99 ], and Germany [ 96 , 102 ] and France [ 69 , 85 ] had two studies each. Single studies were conducted in Colombia [ 67 ], New Zealand [ 107 ], South Korea [ 103 ], Finland [ 63 ], Australia [ 84 ] and Hong Kong [ 91 ].…”
Section: Resultsmentioning
confidence: 99%
“…The result is understandable because the highest drug price for hypnotics was that of lemborexant, followed by suvorexant at the time of this study. Although ORA drug prices are indeed high, a previous study conducted in Japan showed that lemborexant was superior to zolpidem in terms of cost-effectiveness ( 14 ). Therefore, many physicians may prescribe ORAs frequently because of their efficacy and safety despite the high cost of ORA.…”
Section: Discussionmentioning
confidence: 99%
“…Insomnia relates to a number of illnesses, such as hypertension, diabetes, stroke, and chronic kidney illness ( 12 ). Also, insomnia relates to accidents on the road, workplace, and home ( 13 , 14 ). As a significant predictor for anxiety and depression, insomnia has bidirectional effects on anxiety and depression ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%